2011
DOI: 10.1055/s-0031-1297011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cytotoxic Studies of Hydroximino Derivatives of Some 16E-Arylidenosteroids

Abstract: Oxime and dioxime derivatives of various 16E-arylidenosteroids in the androstene series have been prepared and evaluated at the National Cancer Institute (NCI), Bethesda (USA) for their antineoplastic activity against various tumor cell lines in order to determine the structural requirements for cytotoxic activity. Aldol condensation of dehydroepiandrosterone (DHA) and DHA acetate with various aldehydes followed by treatment with hydroxylamine hydrochloride resulted in the formation of 16E-arylidenosteroid-oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Benzylidene derivatives obtained by the Claisen–Schmidt condensation of steroidal ketones may serve as starting materials for the synthesis of compounds of pharmacological importance or may show favourable biological activity themselves . The 16‐arylidene group was found to be a good pharmacophore for cytotoxic activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzylidene derivatives obtained by the Claisen–Schmidt condensation of steroidal ketones may serve as starting materials for the synthesis of compounds of pharmacological importance or may show favourable biological activity themselves . The 16‐arylidene group was found to be a good pharmacophore for cytotoxic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 16‐arylidene derivatives of androst‐5‐en‐3β‐ol‐17‐one and their 4‐aza‐analogues were reported to prevent the progression of lipopolysaccharide‐induced neuroinflammation and subsequent neurodegeneration, so they represent a new class of neuroprotective agents for the treatment of Alzheimer's and Parkinson's diseases . All arylidene derivatives were obtained from the corresponding steroidal 17‐ketones and aromatic aldehydes in base‐catalysed reactions in the presence of lithium diisopropylamide (LDA), KF/Al 2 O 3 , or alkali‐hydroxides …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, A-ring arylideneandrostane derivatives were also described but much less frequently [ 31 , 54 , 55 ]. In addition to cytotoxic effects, several studies reported other biological activities, such as aromatase inhibition, anti-inflammatory, neuroprotective and skeletal muscle relaxing activities and tissue-selective androgen receptor modulator effects [ 38 , 57 , 58 ]. A selection of the most relevant 16 E -arylideneandrostane derivatives is presented in Table 1 .…”
Section: Bioactivity Of 2- and 16 E -Arylideneamentioning
confidence: 99%
“…In this regard, different derivatives of androsterone (3α-hydroxy-5α-androstan-17-one) have been excessively studied as potent anti-cancer agents (Figure 1) [18,19]. Recently, the significant cytotoxic and aromatase inhibitory potential of a large number of androsterone derivatives containing substitution at position 16 have been reported [12,20,21]. Bansal et.…”
Section: Introductionmentioning
confidence: 99%